Coherent Transport in Photonic Lattices: A Survey of Recent Analytic Results - Bossé, E.-O.; Vinet, L. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
The analytic specifications of photonic lattices with fractional revival (FR) and perfect state transfer (PST) are reviewed. The approach to their design which is based on orthogonal polynomials is highlighted. A compendium of analytic models with PST is offered. New results on their FR properties are included. The nearest-neighbour approximation is adopted in most of the review; one analytic example with next-to-nearest neighbour interactions is also presented.